Effect of foreign oxides on the phase structure, sintering and transport properties of Ba0.5Sr0.5Co0.8Fe0.2O3-δ as ceramic membranes for oxygen separation - Ran, R.; Guo, Y.; Gao, D.; Liu, Shaomin; Shao, Z. (Pergamon, 2011)
A series of foreign oxides including CuO, ZnO, NiO, Co2O3 and Al2O3 were investigated as sintering aids to facilitate the densification of Ba0.5Sr0.5Co0.8Fe0.2O3-δ (BSCF) membranes for oxygen separation. The effects of these oxides on the phase structure, sintering behavior, electrical conductivity and oxygen permeability of BSCF oxide were systematically studied by X-ray diffraction (XRD), oxygen temperature-programmed desorption (O2-TPD), environmental scanning electron microscopy (ESEM), four-probe direct current (DC) conductivity and gas permeation measurements. The results showed that reactions between the membrane material and the foreign oxides took place at elevated temperatures. These oxides displayed different sintering behaviors during the sintering process of BSCF perovskite, with obvious improvement demonstrated in the case of CuO, minimal effects observed from ZnO, Co2O3 and NiO samples, and suppressing effects from Al2O3. The electrical conductivity was clearly increased by introducing Co2O3 as a sintering aid, yielding a maximum value of 70 S cm-1 at 900 °C. The oxygen permeation fluxes of the membrane samples from BSCF + NiO (5 wt.%) and BSCF + ZnO (5 wt.%) are comparable to those of pristine BSCF membranes, whereas the fluxes decreased noticeably when the other foreign oxides were introduced.